Handbook of natural colorants - Bechtold, Thomas; Manian, Avinash P.; Pham, Tung (John Wiley & Sons Inc., 2023)
"Colorants can be dyes, pigments, inks, paint, or chemicals. Colorants are used in relatively small quantities but play an important role in many products including textiles, polymers, food and cosmetics. The growing interest and focus on renewable resources, sustainability and replacement of oil-based products are driving forces to adopt natural resources, and there have been significant developments in the research and application of natural colorants as part of the transition to a bio-based economy"-- Provided by publisher.
Keywords: Dyes and dyeing.; Dye plants.; Dyes and dyeing -- Chemistry.; elektronické knihy; electronic books